Comportamento sexual de risco entre homens que fazem sexo com outros homens no Brasil - Gustavo Machado Rocha (2014)
The Brazilian HIV epidemic is considered to be concentrated in certain vulnerable groups, including illicit drug users, sex workers and men who have sex with men (MSM). The main mode of transmission of HIV in the country is through sexual contact, and the population of MSM is at high risk of exposure to the virus, strongly influenced by sexual behavior. This work aims to evaluate sexual risk behavior and associations in a sample of MSM in Brazil. This is a cross sectional study which adopted the technique of Respondent Driven Sampling (RDS) to recruit the participants. MSM aged 18 years and reported having had at least one sexual relationship with another man in the twelve months preceding the interview were invited to participate in the project, residents in the following cities: Manaus, Recife, Salvador, Belo Horizonte, Rio de Janeiro, Santos, Curitiba, Itajai, Brasilia, and Campo Grande. The events were: unprotected receptive anal intercourse (defined as ever stop using condoms during receptive anal sex in the previous six months) and risk behavior score for HIV infection (calculated from information on the number of male partners and condom use during anal intercourse in the past 12 months with steady, casual and commercial partners). Estimates were weighted by the inverse of the probability proportional to the size of the social network informed by the respondent and the proportion of MSM in each city. For all analyzes the significance level was 0.05. Among 3859 individuals interviewed, the majority of the sample consisted of MSM above 24 years of age (62.3%), non-white (72.4%), with less than twelve years of education (72.7%) and single (84.9%). Nearly sixty percent of respondents selfidentified as homosexual, gay or MSM, 27.9 % as bisexual and 12.7 % as heterosexual, and 46.7% initiated sexual activity aged less than 14 years. Most participants (87.0%) reported having more than one sexual partner in the last twelve months. About the type of sexual partner, 63.6 % reported having a stable partner, 78.1% a casual partner and 41.1% a commercial partner, with large overlapping sexual partnerships; 56.2 % had sex only with men and 18.5 % had had sexual intercourse with transvestite in the last 12 months. Of the total of 3859 participants, 3449 (89.4%) reported a history of sex with men in the 6 months preceding the interview. Of these, 36.5% practiced unprotected receptive anal intercourse in the past 6 months. The final logistic regression model revealed that living with a male partner (OR = 1.80 , 95% CI = 1.21 - 2.68), use of illicit drugs (OR = 1.50 , 95% CI = 1.16 - 1.95), have only a stable partner (OR = 2.46 , 95% CI = 1.71 3,54) or stable and casual or commercial (OR = 1.89, 95% CI = 1.42 - 2.52), history of sex with men only (OR = 1.94 , 95% CI = 1.41 - 2.68), having few or no friends that encourages condom use (OR = 1.80; 95% CI = 1.42 - 2.32), self-reported identity as homosexual (OR = 1.58 , 95% CI = 0.98 - 2.60) and consider moderate to high chance of becoming infected with HIV (OR = 1.99 , 95% CI = 1.46 to 2.63) were characteristics independently associated with inconsistent condom use in receptive anal intercourse. Among 3859 participants, 3738 (96.9%) had complete information about the number of sexual partners and condom use in the last 12 months. In this sample, the mean and median risk behavior score for HIV was, respectively, 5.7 and 4 (SD = 4.99). After categorization, 26.0 % of participants had a score of low risk, 54.2 % medium risk and 19.9% high risk for HIV infection. Final model of ordinal logistic regression showed that age less than or equal to 25 years (OR = 1.14, 95% CI = 1.01 - 1.30), higher education (9-11 years: OR = 1.18 , CI 95 % = 1.02 - 1.38; 12 + years: OR = 1.11 , 95% CI = 0.95 - 1.31), self-reported sexual identity as homosexual (OR = 2.68, 95% CI = 2.17 - 3.31) or bisexual (OR = 1.48, 95% CI = 1.18 - 1.85), current frequent alcohol use (OR = 1.31, 95% CI = 1.15 - 1.51) and illicit drug use in the past 6 months (OR = 1.94, 95% CI = 1.69 - 2.24), first sexual intercourse before 15 years of age (OR = 1.42, 95% CI = 1.25 - 1.61), and use local services to meet sexual partners in the last month (OR = 1.81, 95% CI = 1.59 - 2.06) were characteristics significantly associated with greater risk behavior score for HIV. Among 3859 individuals interviewed, 1795 (46.5%) were between 18 and 24 years old, ranging from 24.1% (Santos) and 70.6% (Manaus) in the cities evaluated. Third eight percent practiced unprotected receptive anal intercourse (ranging from 21.0% in Brasilia to 41.9% in Campo Grande) and 44.3% unprotected insertive anal sex (ranging from 29.0% in Brasilia to 50.2% in Manaus) in the last 6 months. In this sample, 25.8%, 53.9% and 20.3% were classified with, respectively, low, medium and high risk behavior score for HIV. Santos was the city where more proportion of young HSH reported history of sexual intercourse under the influence of alcohol (75.9%) or illicit drugs (39.7%), despite high rates in all locations studied. Less than half of the sample of young HSH had already performed serologic tests for HIV and/or syphilis previously, with a smaller proportion in Manaus (22.4% and 8.9%, respectively) and Salvador (31.6% and 17.9%, respectively). Despite widespread access to information and condoms, the proportion of MSM engaged in unprotected sexual practices is very high in the country. Thus, contrary to the assumption of relative stability of the HIV epidemic, there is a great potential for spread of the virus and other sexually transmitted infections in Brazil. The MSM population, as well as other vulnerable populations, has HIV prevalence greater than the general population, with other risk behavior characteristics, including high consumption of alcohol and drugs. In this sense, specific intervention strategies should be developed aimed at this group, with special attention to young MSM, focusing on the importance of anal sex in HIV transmission.